PLS-SEM assessment of the effect of using standardized blocks on artisans’ health in the construction industry - Haruna Domanamwin Abudu; Cecilia Modupe Mewomo; Francis Kwesi Bondinuba; Murendeni Liphadzi; Kofi Owusu Adjei (Journal of Asian Architecture and Building Engineering)
Construction work is physically demanding and poses significant health risks to artisans. This study investigates the impact of masonry units on artisans’ health and work lives. The study used partial least squares structural equation modeling to model the cause and effect of standardized blocks on artisans’ work lives. A quantitative approach was used in this study. The purposive sampling technique played a role in selecting artisans in Kumasi. The sample size led to the selection of 425 masons with a 95% response rate of 402 responses. Descriptive and inferential statistics were used to analyze the results. The findings revealed that lifting, falling, and weather conditions significantly influenced health problems. Bending, twisting, pushing, and pulling negatively affected their health. The model’s predictive power indicated that health problems associated with artisan life recorded Q2 prediction was 0.158 > 0.15, and the R2 value for the effect of health problems was 0.192. This study contributes to health and safety theories in construction. Construction firms and product suppliers should develop a suitable lightweight sandcrete block to minimize potential health risks for workers in the construction industry. The government should also reduce taxes on modern machinery to curb the more physically demanding work in construction.